PEMBUATAN ALAT UJI IMPAK METODE CHARPY DAN IZOD - Asep Rachmat; Nabil Said Basyamchoh; Engkos Koswara (PROCEEDING STIMA)
One of the things that lead to failure of an engine is the strength of the material and pengerjaanya . Material strength is a trait possessed by each material . One way that can be done to determine the material properties by performing the test known. Rapid Loading impact testing is the basis of the manufacture of test equipment, where the gravity force works on a pendulum that is dropped from a height and ending with testing specimens mashing. In this final report , will be developed how to make an impact test instrument that can be used to determine the type of fracture and the price impact of a specimen by using Charpy and Izod . Ie, starting with the selection of materials , measuring , cutting , machining , assembly and eventually test equipment can be used as a testing tool.Keywords: machining, production, impact test